2017
DOI: 10.1016/j.juro.2017.07.072
|View full text |Cite
|
Sign up to set email alerts
|

An Intraprostatic Modified Release Formulation of Antiandrogen 2-Hydroxyflutamide for Localized Prostate Cancer

Abstract: Intraprostatic injections of 2-hydroxyflutamide depot formulations showed antitumor effects, and proved to be safe and tolerable. However, for better anticancer effects higher doses and better dose distribution are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Testosterone levels in plasma remained unaffected, showing that the low systemic exposure to 2-HOF from Liproca Depot over time did not significantly alter the gonadal-pituitary axis. Similar results were seen in a previous Liproca Depot study [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Testosterone levels in plasma remained unaffected, showing that the low systemic exposure to 2-HOF from Liproca Depot over time did not significantly alter the gonadal-pituitary axis. Similar results were seen in a previous Liproca Depot study [12].…”
Section: Discussionsupporting
confidence: 91%
“…Liproca Depot (LIDDS AB, Uppsala, Sweden) is an intraprostatic injection of the antiandrogen 2-hydroxyflutamide (2-HOF) in a calcium sulfate-based depot produced with the NanoZolid (LIDDS AB) drug delivery platform, for which the antiandrogen is slowly released over a period of up to 6 mo [12,13]. Treatment with Liproca Depot is a focal therapy that can be performed in an outpatient urology clinic with local anesthesia and a transrectal procedure similar to prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been used to generate depot-formulations of anti-androgens for use in prostate cancer. 206 NZ-TLR is a TLR9 agonist with an undisclosed TLR9 structure encapsulated within a calcium sulfate excipient (NanoZolid) that permits slow release depot formulation following intra-tumoral dosing obviating the need for frequent dosing. Preclinical data in syngeneic tumor models have been reported but not published with plans for first-in-human clinical trials in 2021.…”
Section: Preclinical and Clinical Studies Of Tlr9 Agonistsmentioning
confidence: 99%
“…Liproca ® Depot (LIDSS Pharma) utilises a drug-delivery platform known as Nanozolid ® for the locoregional treatment of prostate cancer to deliver 2-hydroxyflutamide for up to six months. Nanozolid ® is made of granules of compressed calcium sulfate mixed with non-compressed calcium sulfate hemihydrate powder and is rehydrated at point of use to form an injectable paste [94,95]. An initial burst release is observed from the drug content contained in the non-compressed powder, with the granule-encapsulated drug demonstrating prolonged release.…”
Section: Liproca ®mentioning
confidence: 99%
“…Combined results published from two Phase I/II single-arm interventional clinical trials (NCT00913263 & NCT02341404) (n=47) demonstrated that treatment was overall well tolerated following intra-prostatic administration of drugloaded paste. However, the clinical response was variable across the patient population, indicating that further optimisation on clinical dosing and distribution of this drug delivery platform is required to demonstrate true clinical benefit [95]. Based on the efficacy results from these clinical trials a third clinical trial is underway to assess the potential application of Liproca ® Depot during active surveillance of individuals at high risk of progression of prostate cancer (NCT03348527).…”
Section: Liproca ®mentioning
confidence: 99%